Experimental and numerical investigations of austenitic stainless steel semi-oval hollow sections under combined compression and bending - Li, Shuai (2024)
Semi-oval hollow section is an innovative cross-section profile, including one semi-circular flange, one flat flange and two flat webs. While the semi-circular flange (exposed to fluid or wind) offers a low level of hydrodynamic or aerodynamic drag, the flat elements facilitate connections with other members. This paper presents experimental and numerical investigations into the local buckling behaviour and resistances of austenitic stainless steel semi-oval hollow sections under combined compression and bending. A testing programme was firstly conducted and included initial local geometric imperfection measurements and ten eccentric compression tests. In conjunction with the testing programme, a numerical modelling programme was performed, where finite element models were developed to validate against the test results and conduct parametric studies for expanding the test data pool over a wider range of cross-section dimensions and loading combinations. The obtained test and numerical data were used to evaluate the applicability of the relevant design interaction curves for austenitic stainless steel rectangular hollow sections, as prescribed in the European code and American specification, to austenitic stainless steel semi-oval hollow sections. On the basis of the evaluation results, the codified design interaction curves were found to provide conservative resistance predictions. Finally, an improved design interaction curve, with more accurate end points and suitable shape, was developed and led to more accurate and consistent resistance predictions for austenitic stainless steel semi-oval hollow sections under combined compression and bending.